2015
DOI: 10.1007/s00709-015-0871-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Mentha spicata essential oil in suppression of Aspergillus flavus and aflatoxin contamination in chickpea with particular emphasis to mode of antifungal action

Abstract: The present study reports in vivo antifungal and antiaflatoxigenic efficacy of Mentha spicata essential oil (EO) against toxigenic Aspergillus flavus strain LHP(C)-D6 in chickpea food system up to 12 months of storage. In addition, the mode of antifungal action of EO was also determined to understand the mechanism of fungal growth inhibition. The in vivo study with different concentrations of M. spicata EO showed dose-dependent decrease in fungal colony count as well as aflatoxin B1 concentration. The EO cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 23 publications
2
10
0
1
Order By: Relevance
“…Eucalyptus sp., Ferula galbaniflua, Thymus capitatus and Syzygium aromaticum [71] Curcuma longa [72] Angelica glauca, Plectranthus rugosus, Valeriana wallichii [73] Mentha spicata [74] Michelia alba [75] Ocimum basilicum and Vetiveria zizanioides [76] Artemisia nilagirica [77] Aspergillus fumigatus Rot and mould, aflatoxins production, aspergillosis…”
Section: Rot and Mould Aflatoxins Production Aspergillosismentioning
confidence: 99%
“…Eucalyptus sp., Ferula galbaniflua, Thymus capitatus and Syzygium aromaticum [71] Curcuma longa [72] Angelica glauca, Plectranthus rugosus, Valeriana wallichii [73] Mentha spicata [74] Michelia alba [75] Ocimum basilicum and Vetiveria zizanioides [76] Artemisia nilagirica [77] Aspergillus fumigatus Rot and mould, aflatoxins production, aspergillosis…”
Section: Rot and Mould Aflatoxins Production Aspergillosismentioning
confidence: 99%
“…Da Silva et al [15] reported that Rosmarinus officinalis EO has a strong effect against Fusarium verticillioides, as it showed the ability to rupture the cell wall and inhibit the production of fumonisins. Aspergillus flavus growth and its ability to produce AFs were also significantly affected by treatment with Origanum virens and Ageratum conyzoides EOs in corn and soybeans [16], and using Mentha spicata EO in chickpeas [17].…”
Section: Introductionmentioning
confidence: 99%
“…Many of EOs exhibit antifungal, antibacterial, and antiviral activity (Astani et al, 2010;Khaledi et al, 2015). Several studies investigated the antifungal activity of various EOs against A. flavus (Pekmezovic et al, 2015;Dehghanpour-Farashah and Taheri, 2016;Kedia et al, 2016;Shen et al, 2016;Al-Shahrani et al, 2017). Piperine, a major component of black and long peppers, has been previously demonstrated as an AFB 1 biosynthesis inhibitor.…”
Section: Essential Oils Polyphenols and Alkaloidsmentioning
confidence: 99%